152k views
0 votes
Help?!?!?please?!?!?

Help?!?!?please?!?!?-example-1
User Meteore
by
4.9k points

2 Answers

4 votes

Answer:

D

Explanation:

note that (f - g)(x) = f(x) - g(x)

f(x) - g(x)

= 4x - 3 - (x + 4)

= 4x - 3 - x - 4 ← collect like terms

= 3x - 7 → D

User Denisse
by
4.6k points
4 votes

Answer: OPTION D

Explanation:

To solve the exercise shown in the image attached you must subtract the functions f(x) and g(x), as you can see below:


(f-g)(x)=4x-3-(x+4)

Distribute the negative sign and then you must add like terms. Therefore, you obtain:


(f-g)(x)=4x-3-x-4\\(f-g)(x)=3x-7

User Livibetter
by
5.2k points